Factors affecting engineering students’ self-perceived employability in Morocco - Sabri, Zineb; Remaida, Ahmed; Abdellaoui, Benyoussef; Ait Madi, Abdessalam; Qostal, Aniss; Chadli, Fatima Ezzahra; Fakhri, Youssef; Moumen, Aniss (International Journal of Evaluation and Research in Education (IJERE), 2025)
In a dynamic socio-economic world, perceiving a career opportunity and job prospects has become complex. The number of unemployed individuals is rising despite the increasing number of students pursuing higher education. This study is suggested to enhance students’ professional insertion, guide their career development initiatives, and help them acquire the skills demanded by prospective employers, thereby increasing their likelihood of employment. For this goal, this study investigates the determinants impacting self-perceived employability (SPE) among engineering students. Following a quantitative approach to explain how personal and contextual factors impact perceived employability, more than 350 Moroccan engineering students responded to a questionnaire for data collection, which had an internal consistency of 0.90. Data analysis employing advanced statistical techniques using structural equations modeling (SEM) to conduct descriptive, regression, and mediation analysis. The findings highlight that academic performance, university contribution, and personal circumstances significantly influence perceived employability, while generic skills have a minor effect. Furthermore, personal determinants are identified as stronger than contextual ones. The results provide several recommendations to stakeholders such as university administrations, teaching staff, employers, the Ministry of Education, and graduates. Additionally, they offer an insightful exploration of the intricate interactions among factors that enhance employability.